Palindromic Rheumatism Frequently Precedes Early Rheumatoid Arthritis: Results From an Incident Cohort. Issue 10 (21st October 2019) - Ellingwood, L.; Schieir, O.; Valois, M. F.; Bartlett, S. J.; Bessette, L.; Boire, G.; Hazlewood, G.; Hitchon, C.; Keystone, E. C.; Tin, D.; Thorne, C.; Bykerk, V. P.; et al.
Abstract : Background: This multicenter incident cohort aimed to characterize how often early rheumatoid arthritis (ERA) patients self‐report episodic joint inflammation (palindromic rheumatism) preceding ERA diagnosis and which characteristics differentiate these patients from those without prior episodic symptoms. Methods: Data were from patients with early confirmed or suspected RA (more than 6 weeks and less than 12 months) enrolled in the Canadian Early ArThritis CoHort (CATCH) between April 2017 to March 2018 who completed study case report forms assessing joint pain and swelling prior to ERA diagnosis. Chi‐square and t tests were used to compare characteristics of patients with and without self‐reported episodic joint inflammation prior to ERA diagnosis. Multivariable logistic regression was used to identify sociodemographic and clinical measures associated with past episodic joint inflammation around the time of ERA diagnosis. Results: A total of 154 ERA patients were included; 66% were female, and mean (SD) age and RA symptom duration were 54 (15) years and 141 (118) days. Sixty‐five (42%) ERA patients reported a history of episodic joint pain and swelling, half of whom reported that these symptoms preceded ERA diagnosis by over 6 months. ERA patients with past episodic joint inflammation were more often female, had higher income, were seropositive, had more comorbidities, fewer swollen joints, and lower Clinical Disease Activity Index (CDAI) around the time of ERA diagnosis ( P < 0.05). These associations remained significant in multivariable regression adjusting for other sociodemographic and RA clinical measures. Conclusion: Almost half of ERA patients experienced episodic joint inflammation prior to ERA diagnosis. These patients were more often female, had higher income, and presented with milder disease activity at ERA diagnosis.